2020
DOI: 10.1021/acschemneuro.0c00338
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Molecular Dynamics and Metadynamics Simulation Studies of the Binding and Unbinding Mechanism of TTR Stabilizers AG10 and Tafamidis

Abstract: Amyloid transthyretin (ATTR) amyloidosis is a widespread and fatal systemic amyloidosis characterized by the misfolding and amyloid aggregation of transthyretin (TTR). Studies suggest that dissociation of the TTR tetramer is the key step for its misfolding. Because of the importance of tetramer dissociation on ATTR amyloidosis, many TTR stabilizers have been discovered to stabilize the tetramer structure. This paper describes the application conventional molecular dynamics and metadynamics simulations to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Molecular dynamics (MD) simulations allow studying the structural dynamics of biological systems at atomic resolution . MD simulations are especially useful in modeling and assessing the binding capacity of small molecules to target proteins since they not only provide atomic information on the interaction but also allow estimation of the binding energetics. , MD simulations have been used to investigate the impact of mutations on TTR conformational flexibility , and to investigate the mechanism of TTR protection by existent kinetic stabilizers. However, to the best of our knowledge, MD-based methods for estimating binding affinities have not been employed to assist in the design of novel molecules aimed to interact with T 4 -binding sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics (MD) simulations allow studying the structural dynamics of biological systems at atomic resolution . MD simulations are especially useful in modeling and assessing the binding capacity of small molecules to target proteins since they not only provide atomic information on the interaction but also allow estimation of the binding energetics. , MD simulations have been used to investigate the impact of mutations on TTR conformational flexibility , and to investigate the mechanism of TTR protection by existent kinetic stabilizers. However, to the best of our knowledge, MD-based methods for estimating binding affinities have not been employed to assist in the design of novel molecules aimed to interact with T 4 -binding sites.…”
Section: Introductionmentioning
confidence: 99%
“… 49 , 50 MD simulations have been used to investigate the impact of mutations on TTR conformational flexibility 51 , 52 and to investigate the mechanism of TTR protection by existent kinetic stabilizers. 53 55 However, to the best of our knowledge, MD-based methods for estimating binding affinities have not been employed to assist in the design of novel molecules aimed to interact with T 4 -binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…Diflunisal acted as a tetramer stabilizer for the treatment of ATTR-CM, as the associated survival benefits were reported to be similar to those of Tafamidis (Maurer et al, 2018 ; Ibrahim et al, 2022 ). AG10 stabilized TTR tetramer by forming H-bonds with S117 (Zhou et al, 2020 ), and AG10 treatment was well-tolerated, achieved target plasma concentrations, and demonstrated near-complete stabilization of TTR (Judge et al, 2019 ; Nelson et al, 2021 ). In this work, it was found that E61K-TTR homozygous proteins and E61K: WT-TTR heterozygous tetramers might respond to current kinetic stabilizers less effectively compared to WT-TTR because full inhibition of fibril formation could be achieved for WT-TTR based on previously reported in vitro results.…”
Section: Discussionmentioning
confidence: 99%
“…AG10 has a somewhat different mechanism of stabilization from tafamidis in that it was designed to mimic the structural form of the TTR “super-stabilizer” variant, T119M. AG10 forms hydrogen bonds with serine residues at the same site as the T119M variant and, based on assays of stabilization, it is believed to be a more potent stabilizer of TTR than is tafamidis ( 9 , 10 ). However, a major problem in theorizing improved efficacy of TTR stabilizers based on assays of stabilization is that there are several assays and all are performed under nonphysiologic conditions.…”
mentioning
confidence: 99%